The Impact of Supply Chain Innovation and Market Collaboration on the Competitive Advantage of Agribusiness MSMEs in the Era of Digital Transformation - Donny Ivan Samuel Simatupang; Putu Fajar Kartika Lestari (Westscience Press, 2026)
The era of digital transformation has created significant opportunities and challenges for agribusiness micro, small, and medium enterprises (MSMEs), particularly in strengthening their competitive advantage through innovation and collaboration. This study aims to analyze the impact of supply chain innovation and market collaboration on the competitive advantage of agribusiness MSMEs using a quantitative approach. Primary data were collected from 155 respondents through a structured questionnaire measured using a five-point Likert scale. Data analysis was conducted using SPSS version 25, including validity and reliability testing, classical assumption tests, and multiple linear regression analysis. The results indicate that supply chain innovation has a positive and significant effect on competitive advantage, while market collaboration also shows a significant positive influence. Simultaneously, both variables contribute significantly to competitive advantage with an R² value of 0.610, indicating that 61.0% of the variance in competitive advantage is explained by the model. These findings highlight the importance of integrating innovative supply chain practices and strengthening collaborative networks to enhance business performance in the digital era. The study provides practical implications for policymakers and agribusiness practitioners in designing strategies that promote digital adoption, partnership development, and sustainable competitiveness.